Cu(I) Modification during γ-Fe2O3 Nanoparticles Synthesis and Subsequent Characterization - Hong Mao; Xiaoyan Qiu; Decai Li; Yueqiang Lin; Xiaodong Liu; Jian Li (Journal of Chemistry)
During the synthesis of the γ-Fe2O3 nanoparticles via the chemically induced transition method, Cu(I) modification has been attempted by adding CuCl/NaOH to the treatment solution. The experimental results showed that, under the condition of a NaOH content equal to 0.04 moles, when the content of CuCl is as low as 1.25×10-3 or 2.50×10-3 moles, the products are single γ-Fe2O3/Cu(I)FeO2/FeCl3·6H2O composite nanoparticles, whereas when the content of CuCl is higher, 5×10-2 moles, the product is a mixture consisting of γ-Fe2O3/Cu(I)FeO2/FeCl3·6H2O nanoparticles and Cu(II)(OH)Cl nanoparticles. For the γ-Fe2O3/Cu(I)FeO2/FeCl3·6H2O composite nanoparticles, the Cu(I)FeO2 interface layer is not thick enough to form one unit cell, but it can modify the formation of a FeCl3·6H2O surface layer and the effective magnetization of the γ-Fe2O3 core.